Empowering Community Health Volunteers: Enhancing Early Stunting Detection through Knowledge and Skill Development in Indonesia’s 3T Regions - Fatimah, Siti Nur (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
Stunting remains a persistent public health issue in Indonesia, particularly in rural and 3T (Terdepan, Terluar, Tertinggal) regions. Posyandu cadres, as community health volunteers, are positioned to play a pivotal role in the early detection of stunting. This study examines how knowledge and skill development interventions improve cadres’ capacity for early stunting detection. Using a qualitative descriptive design, this study synthesizes findings from eight empirical studies and relevant national data. Thematic analysis was applied to examine the effects of training programs on cadre knowledge acquisition, skill proficiency, and community health outcomes. The research further assesses frameworks appropriate for analog 3T contexts, including logistical, cultural, and policy considerations. Key results demonstrate a statistically significant improvement in cadre knowledge following training interventions, with a strong correlation (r = 0.80) between knowledge gains and improved stunting detection skills. Enhanced competencies led to reductions in community stunting cases, improved parental health behaviors, and greater community engagement. Barriers such as geographic isolation and cultural resistance were identified, underscoring the need for tailored training and ongoing supervision. The findings emphasize the importance of institutionalizing sustainable training models, supported by cross-sectoral policy frameworks. Posyandu cadres, when properly trained and supported, serve as critical agents in Indonesia’s mission to reduce childhood stunting. Community-integrated, scalable interventions are essential to extend this impact across underserved regions.